2009
DOI: 10.1063/1.3259390
|View full text |Cite
|
Sign up to set email alerts
|

Eu oxidation state in fluorozirconate-based glass ceramics

Abstract: The influence of InF 3 doping and remelting on Eu-doped fluorozirconate-based glass ceramics was investigated using near-edge x-ray absorption and optical spectroscopy. It was found that the addition of InF 3 to the melt decreases the Eu 2+ / Eu 3+ mole ratio, while remelting leads to a significant change in the Eu 2+ / Eu 3+ ratio in favor of Eu 2+ . Photoluminescence spectroscopy shows that additional annealing steps lead to the formation of BaCl 2 nanoparticles in the glass. In as-made glass ceramics contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…Two main peaks A and B may be tentatively associated with Ba-Zr and Na-Zr compounds respectively, while the low temperature crystallization peak D is known to appear in the presence of chlorine, and corresponds to a quasi-superposition of an initial glass transition followed immediately by a partial crystallization of Cl-enriched phase of the glass, leading to the formation of BaCl 2 nanocrystals inside the host glass. This superposition of the glass transition and crystallization regions may vary substantially with the concentration of Cl [11,12] and is discussed later below. It can be clearly seen that there is a large temperature range between the crystallization of the Cl-enriched phase, peak D, and the beginning of the total crystallization of the glass, peak A.…”
Section: Resultsmentioning
confidence: 96%
“…Two main peaks A and B may be tentatively associated with Ba-Zr and Na-Zr compounds respectively, while the low temperature crystallization peak D is known to appear in the presence of chlorine, and corresponds to a quasi-superposition of an initial glass transition followed immediately by a partial crystallization of Cl-enriched phase of the glass, leading to the formation of BaCl 2 nanocrystals inside the host glass. This superposition of the glass transition and crystallization regions may vary substantially with the concentration of Cl [11,12] and is discussed later below. It can be clearly seen that there is a large temperature range between the crystallization of the Cl-enriched phase, peak D, and the beginning of the total crystallization of the glass, peak A.…”
Section: Resultsmentioning
confidence: 96%
“…Due to the low Eu-doping level of 3 mol%, the R value is set to 1.5, which was determined for dilute systems from an “in situ” XANES analysis of electrochemical conversion between Eu 2+ and Eu 3+ in a EuCl 3 solution [5]. For the Eu-doped FCZ glasses the curve fitting results and the calculated mole fractions are listed in [2]. …”
Section: Methodsmentioning
confidence: 99%
“…In such a complex system, the addition of each new chemical and each change in processing affects the material properties. In an earlier work on Eu-doped FCZ glass ceramics, the influence of InF 3 and remelting on the Eu 2+ -to-Eu 3+ ratio was investigated [2]. It was shown that the addition of InF 3 decreases the Eu 2+ -to-Eu 3+ ratio whereas remelting increases the Eu 2+ -to-Eu 3+ ratio.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that Eu 3+ -ions delivering the red luminescence are preferably localized in the amorphous glass, while the Eu 2+ -ions emitting in the blue-green region become dominating after partial crystallization of the glass. The results published in [6] showed that the significant amount of Eu 3+ -ions is always present in fluorozirconate based glass ceramics reducing the performance of these materials as both scintillators and storage phosphors. Besides Eu luminescence, strong UV luminescent band was observed in barium disilicate phosphore at the doping with Pb ions [7].…”
Section: Introductionmentioning
confidence: 96%